Quantifying the Uncertainties in an Ensemble of Decadal Climate Predictions. Issue 24 (22nd December 2017) - Strobach, Ehud; Bel, Golan
Abstract: Meaningful climate predictions must be accompanied by their corresponding range of uncertainty. Quantifying the uncertainties is nontrivial, and different methods have been suggested and used in the past. Here we propose a method that does not rely on any assumptions regarding the distribution of the ensemble member predictions. The method is tested using the Coupled Model Intercomparison Project Phase 5 1981–2010 decadal predictions and is shown to perform better than two other methods considered here. The improved estimate of the uncertainties is of great importance both for practical use and for better assessing the significance of the effects seen in theoretical studies. Key Points: Improved estimation of decadal climate prediction uncertainties No assumptions regarding the distribution of the ensemble predictions Improved estimation also for weighted ensembles